Dukungan Keluarga Berhubungan Dengan Kepatuhan Hemodialisis pada Pasien Gagal Ginjal Kronik (GGK): Literature Review: Family Support and Hemodialysis Compliance in Patients with Chronic Renal Failure: Literature Review - Jumain Jumain; Parmi Parmi; Agustinus Talindong; Wahyu Wahyu (Journal of Health, 2023)
Introduction: Chronic Kidney Disease (CKD) is a disease that is progressive and irreversible in kidney function. Decreased kidney function has an impact on fluids and metabolic waste accumulating in the body. So that it will affect the fluid balance resulting in uremia and excessive amounts of nitrogen waste products in the blood cycle. One of the contributions to the failure of hemodialysis is related to patient compliance in undergoing the program. Objective: To determine the relationship between family support and adherence to hemodialysis in CRF patients. Method: This study used the systematic literature review method, this study used 55 articles obtained through identification searches, interpretation of all studies and assessing articles, searches began on June 24 to July 29, 2022. Results: Obtained 10 research findings articles that were still relevant, after conducting an analysis of the articles it was found that there was a relationship between family support and compliance in undergoing hemodialysis therapy including gender, education, age, motivation, knowledge, duration of hemodialysis, access to health services and family support. Conclusion: based on the article, it can be concluded that there is a relationship between family support and adherence to undergoing hemodialysis in chronic kidney failure (CKD) patients. This article can have a good impact on the management of family support with adherence to undergoing hemodialysis in chronic kidney failure (CKD) patients.Keywords: